Pengaruh Harga, Promosi Dan Inovasi Kemajuan Teknologi Terhadap Keputusan Pembelian Smartphone Pada Toko King Sell Kota Rantau Prapat - Mhd Faisal Anwar Afandi Rambe; Yenni Samri Juliati Nasution; Khairina Tambunan (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to test whether there is an influence of price, promotion and technological innovation on purchasing decisions at the King Sell store in the city of Rantau Prapat. The population subjects of this research are all consumers of the King Sell shop in the city of Rantau Prapat in May and the object of this research population is the decision to purchase smartphones at the King Sell shop in the city of Rantau Prapat. The sample was taken from 100 respondents using the Slovin formula. The data collection technique was carried out by filling out a questionnaire which was filled in directly by consumers of the King Sell Rantau Prapat shop. The data analysis techniques used are validity testing, reliability testing, classical assumption testing, multiple linear regression analysis and using hypothesis testing, namely Partial Test (T Test), Simultaneous Test (F Test) and Determination Coefficient Test (R2). The results of the research show that the data is valid, reliable, normally distributed, not heteroscedastic and there are no symptoms of multicollinearity so that it can be analyzed using multiple linear regression and produces a value of Y = 2.216 + 0.204X1 +0.419X2 + 0.224X3. The results of the T test show that the significant value of each independent variable is smaller than 0.05 (price sig. 0.007; promotion sig. 0.000; innovation sig. 0.020) which means that price, promotion and innovation have their respective influences on decisions. purchase. The F test results show that the sig value. The F test is smaller than the sig value. (0.000 < 0.05) which means that there is an influence of the independent variable on the dependent variable simultaneously. And the coefficient of determination test shows that the R2 value is 0.407. This shows that there is an influence of price (X1), promotion (X2) and innovation (X3) on the purchasing decision (Y) of smartphones at the King Sell store in Rantau Prapat city of 40.7%, while the remaining 59.3% is influenced by other variables outside this research model.